2008
DOI: 10.1111/j.1540-8175.2008.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Real Time Three‐Dimensional Echocardiography in Patients with Hypertrophic Cardiomyopathy: Comparison with Two‐Dimensional Echocardiography and Magnetic Resonance Imaging

Abstract: In patients with HCM, RT3DE demonstrated superior performance than 2DE for the evaluation of myocardial hypertrophy, LV volumes, LVEF, and LV mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…85 LEOPARD (lentigines, ECG abnormalities, ocular hypertelorism, pulmonary stenosis, abnormal genitalia, growth retardation, and deafness) syndrome shares many features with Noonan syndrome and is also caused by mutations in the PTPN11 gene. 23 Noonan syndrome and LEOPARD syndrome are examples of neurocardio-facial-cutaneous syndromes. Many are caused by germline mutations in key components of the highly conserved RAS-MAPK cascade.…”
Section: Desai Et Al Hypertrophic Cardiomyopathy 161mentioning
confidence: 99%
See 1 more Smart Citation
“…85 LEOPARD (lentigines, ECG abnormalities, ocular hypertelorism, pulmonary stenosis, abnormal genitalia, growth retardation, and deafness) syndrome shares many features with Noonan syndrome and is also caused by mutations in the PTPN11 gene. 23 Noonan syndrome and LEOPARD syndrome are examples of neurocardio-facial-cutaneous syndromes. Many are caused by germline mutations in key components of the highly conserved RAS-MAPK cascade.…”
Section: Desai Et Al Hypertrophic Cardiomyopathy 161mentioning
confidence: 99%
“…Three-dimensional echocardiography quantifies and characterizes myocardial hypertrophy, LV volumes, LV ejection fraction, and LV mass more accurately than traditional 2D echocardiography. 23 Cardiac magnetic resonance (CMR) is especially useful in identifying the varied phenotypic presentations of HCM, particularly when hypertrophy involves the anterolateral free wall 24 and apical variant, 25 which often are poorly visualized on echocardiography. In 1 study, 24 CMR accurately identified HCM missed on echocardiography in 6% of the patients.…”
Section: Geometrymentioning
confidence: 99%
“…The 3D echocardiographic assessment of LV volumes and function provides accuracies that approach the accuracy of cardiac magnetic resonance imaging (cMRI) [6][7][8][9][10][11][12][13][14]. Furthermore, 3D echocardiography for the assessment of LV volumes and ejection fraction (EF) has been currently recommended over the use of 2D echocardiography, due to its accuracy and reproducible measurements [13,14].…”
Section: Assessment Of the Left Ventriclementioning
confidence: 99%
“…The real-time three-dimensional echocardiography allows detailed evaluation of the morphological changes undergone by the LV in HCM, with performance comparable to MRI and notably better than two-dimension echocardiography 63 .…”
Section: Three-dimensional Echocardiographymentioning
confidence: 99%